Morphometric measurement of the cervical spine for minimally invasive pedicle screw fixation using reverse engineering and three‐dimensional reconstruction - Zhou, Zi‐Jia; Wen, Chao‐Lun; Sun, Qin‐Min; Wang, Ai‐Ping; Yan, Zheng‐Guang; Liu, Fang; Chen, Xi; Cao, Qi; Zhou, Xiao‐Bing; Tan, Jian‐Guo; Li, Yan‐Bing (The international journal of medical robotics + computer assisted surgery, 2017)
Background Percutaneous cervical pedicle screw fixation has been proven to be an effective method of cervical screw instrumentation, which has the advantages of less invasiveness and low blood loss. Emerging evidence has indicated that the cervical spinous process plays an important role in percutaneous spine surgery. However, there is a limited amount of information on the fundamental research of pedicle and its associated imaging parameter measurement. The purpose of this study was to measure the anatomic data of the pedicle screw channel (PSC) using reverse engineering and three‐dimensional reconstruction, and also to discuss the three‐dimensional relationship between the cervical spinous process and the pedicle screw channel. Methods Twenty adult subjects (10 males, 10 females, age range 19–46 years) were studied using the method of three‐dimensional CT reconstruction and reverse engineering. The centrum was divided into 10 equal parts from front to back. The bisectors were defined as borderline depths of the centrum, from front to back, 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, 0% of borderline depths were presented. Then, a 3D coordinate system was constructed to measure all the data, including the radius of the inscribed circle, the length of the PSC, the insertion angle, the distances from entry point to cervical spinous process and skin depth. All the indexes were measured from 70% to 90% borderline depth. Results The radius of the inscribed circles from C3 to C7 at 90% borderline depth were 2.94 ± 0.55 mm, 3.04 ± 0.40 mm, 3.15 ± 0.36 mm, 3.28 ± 0.47 mm, 3.89 ± 0.54 mm, respectively. The lengths of the PSC were between 25 and 32 mm. The insertion angles for 70% to 90% borderline depth were 28.33°, 34.28°, 37.92°, respectively. The relationship between the PSC and spinous process was measured as the distance from the entry point to the end of the spinous process, which were, respectively, 26.91 mm, 28.18 mm, 30.03 mm, 35.67 mm, 41.99 mm from C3 to C7.The distance from the skin to the entry point of C3‐7 increased gradually. Conclusions The measurements of this study could provide detailed information for percutaneous cervical screw fixation. The data of the relationship between the cervical spinous process and the pedicle screw channel present valuable technical information for the design, optimization and clinical application of the aiming device for percutaneous cervical pedicle screw fixation. Copyright © 2016 John Wiley & Sons, Ltd.